2016
DOI: 10.3892/ol.2016.5124
|View full text |Cite
|
Sign up to set email alerts
|

Radiation induces the generation of cancer stem cells: A novel mechanism for cancer radioresistance

Abstract: Radioresistance remains a major obstacle for the radiotherapy treatment of cancer. Previous studies have demonstrated that the radioresistance of cancer is due to the existence of intrinsic cancer stem cells (CSCs), which represent a small, but radioresistant cell subpopulation that exist in heterogeneous tumors. By contrast, non-stem cancer cells are considered to be radiosensitive and thus, easy to kill. However, recent studies have revealed that under conditions of radiation-induced stress, theoretically ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
53
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(55 citation statements)
references
References 99 publications
(110 reference statements)
1
53
0
1
Order By: Relevance
“…One of the causes of tumor recurrence and metastasis is that cancer cells acquire radioresistance (RR) during fractionated irradiation (7). It has been reported that RR is acquired in various cancer types, including head and neck cancer, non-small cell lung cancer, breast cancer and PCa (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…One of the causes of tumor recurrence and metastasis is that cancer cells acquire radioresistance (RR) during fractionated irradiation (7). It has been reported that RR is acquired in various cancer types, including head and neck cancer, non-small cell lung cancer, breast cancer and PCa (8)(9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%
“…Radiation tolerance is a major factor related to failure of radiotherapy and poor prognosis for cancer patients. Therefore, radiotherapy resistance has become a major obstacle to overcome [10,11].…”
Section: Discussionmentioning
confidence: 99%
“…Radiotherapy is considered as a standard treatment for primary and advanced PCa. However, 20-40% of high-risk PCa patients experience tumor recurrence or distant metastases with one of the causes is radioresistance (3)(4)(5). It has been reported that radioresistance cell reduces the production of reactive oxygen species [ROS; (6)], increases the activation of DNA repair (7), and demonstrates high migratory and invasive abilities (8).…”
Section: Introductionmentioning
confidence: 99%